A visible and label-free colorimetric sensor for miRNA-21 detection based on peroxidase-like activity of graphene/gold-nanoparticle hybrids. Issue 9 (12th February 2016) - Zhao, Huimin; Qu, Yanping; Yuan, Fang; Quan, Xie
Abstract : A visible label-free colorimetric sensor for microRNA-21 detection was developed based on the peroxidase-like activity of graphene/gold-nanoparticle hybrids which was flexibly controlled by using single-stranded PNA-21. Abstract : A visible and label-free colorimetric sensor for microRNA-21 (miRNA-21) detection was developed based on the peroxidase-like activity of graphene/gold-nanoparticle (Au-NP) hybrids which could be flexibly controlled by using single-stranded PNA-21 (ssPNA-21). The spontaneous absorption of ssPNA-21 on graphene/Au-NP hybrid surfaces causes the peroxidase-like catalytic activity of hybrids to be almost completely deactivated via π–π stacking interactions between ssPNA and graphene, so that TMB could not be oxidized to oxTMB in the presence of H2 O2, leading to no color change. The addition of miRNA-21 triggered a hybridization reaction between the PNA probe (ssPNA-21) and miRNA-21. The decrease of the exposed base groups could lead to the release of PNA/DNA duplexes from the hybrid surface, which would restore the catalytic activity of hybrids with a concomitant colorless-to-blue color change. As a result, this sensor emitted a low background signal and responded linearly to miRNA-21 from 10 nM to 0.98 μM with a detection limit of 3.2 nM (S/N = 3) under the optimal conditions. In addition, the biosensor could be also extended to miRNA-21 detection in human serum. Therefore, this colorimetric sensor platform is a potential alternative assay for miRNA detection in biomedical research.